2022
DOI: 10.1111/aje.13056
|View full text |Cite
|
Sign up to set email alerts
|

Low diversity of fishes in high elevation Afrotromontane streams renders them unsuitable for biomonitoring

Abstract: Most of the rivers in the Afrotropics emerge from forested uplands that are prime for human activities, including crop farming, grazing and settlement. However, streams draining these areas have a low diversity of fishes, which limits their use as indicators of water quality and ecological status. Here, we developed macroinvertebrate-and fish-based indices of biotic integrity and evaluated their responses to human activities in the Sondu-Miriu River, Kenya. Overall, water quality declined downstream because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 93 publications
0
4
1
Order By: Relevance
“…It was, however, narrower than the 0.2 to 1.7 reported in the Upper Awash River, Ethiopia [40] and much higher than the 0.04 to 0.33 range reported in River Sondu Miriu [35]. The Shannon-Weiner diversity index (H′) range of 0.54 to 1.36 observed in this study is close to those reported in studies of River Sondu Miriu (0.23 to 1.98) [35] and 0.14 to 0.80 reported in Upper Awash River, Ethiopia [35] [39]. The zero species richness, Simpson's index (D), Shannon-Weiner index (H′), and Pielou's evenness index (J) observed in the upper zone of Awach Kibuon River was also reported in the impacted Upper Awash River, Ethiopia [40].…”
Section: Fish Diversity Indicescontrasting
confidence: 57%
See 2 more Smart Citations
“…It was, however, narrower than the 0.2 to 1.7 reported in the Upper Awash River, Ethiopia [40] and much higher than the 0.04 to 0.33 range reported in River Sondu Miriu [35]. The Shannon-Weiner diversity index (H′) range of 0.54 to 1.36 observed in this study is close to those reported in studies of River Sondu Miriu (0.23 to 1.98) [35] and 0.14 to 0.80 reported in Upper Awash River, Ethiopia [35] [39]. The zero species richness, Simpson's index (D), Shannon-Weiner index (H′), and Pielou's evenness index (J) observed in the upper zone of Awach Kibuon River was also reported in the impacted Upper Awash River, Ethiopia [40].…”
Section: Fish Diversity Indicescontrasting
confidence: 57%
“…Sondu-Miriu, and Yala rivers [25] and 0.44 to 0.78 range reported in Ganjiang River, Jiangxi, China [14]. It was, however, narrower than the 0.2 to 1.7 reported in the Upper Awash River, Ethiopia [40] and much higher than the 0.04 to 0.33 range reported in River Sondu Miriu [35]. The Shannon-Weiner diversity index (H′) range of 0.54 to 1.36 observed in this study is close to those reported in studies of River Sondu Miriu (0.23 to 1.98) [35] and 0.14 to 0.80 reported in Upper Awash River, Ethiopia [35] [39].…”
Section: Fish Diversity Indicesmentioning
confidence: 68%
See 1 more Smart Citation
“…While Amphilius grandis is reported to occur in both the Tana and Northern Ewaso Ng'iro drainages this species is found in higher elevation streams in the Tana drainage than in the Northern Ewaso Ng'iro. Recent studies have also shown that fishes in these Afrotropical higher elevation streams may not be the best indicators of ecosystem health since they are naturally species poor communities (Kleynhans, 1999; Mangadze et al, 2016; Masese et al, 2020; Raburu et al, 2022). Unfortunately, no collections were made at these localities prior to the 1990s so we are unable to determine if the low species richness in these rivers is the natural state or a result of species introductions (i.e., non‐native trout) or land use changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, macroinvertebrates have many practical advantages for bioassessments, including a wide distribution in most streams and rivers, ease of sampling and identification at the family level, and the sampling equipment is relatively inexpensive (Rosenberg and Resh, 1993;Barbour et al, 1999;Bonada et al, 2006). However, in the Afrotropics, high-elevation, low-order streams have a very low diversity of fishes (Kleynhans, 1999;Mangadze et al, 2016;Raburu et al, 2022), which is the alternative bioindicator group for use in river ecosystems (Barbour et al, 1999). This low diversity of fishes makes macroinvertebrates the only best alternative available biotic group for biomonitoring headwater or high-elevation streams.…”
Section: Introductionmentioning
confidence: 99%